2017
DOI: 10.3390/met7100445
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Strain on the Formation of an Intermetallic Layer in an Al-Ni Laminated Composite

Abstract: Abstract:In the present work, the influence of strain on phase formation at the Al/Ni interface was investigated during cold roll bonding and annealing. A sandwich sample composed of an Al-Ni-Al stack was cold rolled with reductions in the range of 50% to 90%, followed by annealing at 450 • C for 60 min. The crystallography of the annealed sandwich samples was analyzed by XRD (X-ray diffraction), whereas the microstructure was studied by scanning electron microscopy, equipped with EDS (energy dispersive spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 48 publications
2
2
0
Order By: Relevance
“…The results from the electron microprobe analyzer showed that the phase had a composition of 75 at% aluminum and 25 at% nickel, consistent with the Al 3 Ni phase composition. The layer grew discontinuously along the interface, but was observed to become continuous with increasing heat treatment time, consistent with the observation made in other studies [23,24].…”
Section: Characteritics Of the Post-rolling Heat Treated Compositessupporting
confidence: 92%
See 2 more Smart Citations
“…The results from the electron microprobe analyzer showed that the phase had a composition of 75 at% aluminum and 25 at% nickel, consistent with the Al 3 Ni phase composition. The layer grew discontinuously along the interface, but was observed to become continuous with increasing heat treatment time, consistent with the observation made in other studies [23,24].…”
Section: Characteritics Of the Post-rolling Heat Treated Compositessupporting
confidence: 92%
“…However, as seen in Figure 6b, with increasing heat treatment time, fewer particles could be observed inside the layer. Similar bright particles inside the Al 3 Ni layer have not been reported in other studies where the Al 3 Ni phase have been closely analyzed [23,24]. The bright particles were not subjected to any further analysis in the current study, since the work is focusing on the relationship between the Al-Ni IMP layers and the bond strength.…”
Section: Characteritics Of the Post-rolling Heat Treated Compositessupporting
confidence: 75%
See 1 more Smart Citation
“…Bimetallic laminated materials have received a lot of attention as a result of their excellent properties [1][2][3][4][5][6]. Better performance is acquired by the combination of advantages from the component materials.…”
Section: Introductionmentioning
confidence: 99%